Aplikasi Sistem Informasi Pendaftaran Siswa Baru Di Sekolah Negeri di Aceh Timur Berbasis Web - mutammimul Ula; Veri Ilhadi; Arief Rahman; Irma Yurni; Emi Maulani (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2024)
The New Student Registration Information System is a very important and digital platform designed to facilitate the process of registering new students at educational institutions. The system developed is expected to increase efficiency, transparency and accessibility in the new student registration process, while reducing administrative burden and manual data errors. Pante Bidari 2 Public Middle School in East Aceh does not yet have a full role for information technology in supporting the smooth running of school activities related to . This system is also very useful for the school, specifically the committee or teachers who are authorized to carry out the process of admitting new students so that the procedures and process for admitting new students run smoothly more effectively and efficiently. Stages in collecting observation data, literature study and conducting interviews during research activities. The aim of this research is to create a Web-based New Student Admissions Information System to make it easier for prospective students and the school in the process of registering and accepting new students. The result of this research is that you can manage new student admission data easily. The web-based New Student Admissions Information System is a technological solution designed to modernize the process of admitting new students to educational institutions. This system also supports transparency and accuracy of information related to the registration process, such as requirements, test schedules, registration fees, and graduation announcements. Implementation of this system has been proven to increase efficiency and minimize errors that often occur in manual processes, while making it easier for prospective students to register students.